Zaman Ledakan Maklumat dan Kemajuan Pengetahuan Dalam Kerangka Pandangan Hidup Islam - Badron, Mohd Sani (Afkar: Jurnal Akidah dan Pemikiran Islam, 2009)
An era of information explosion correlates with the problems of â€œtoo much information effectâ€ and â€œthe information overloadâ€. The fundamental issue is that, humankind has too many choices of information, too much of the time; human beings are even informing themselves to the death of their humanity. Its solution lies in grasping the basic idea that, firstly, there is difference between information, science, understanding, and wisdom, secondly, in order that it could be properly understood, true knowledge requires adab towards it, which accords with fardu â€˜ayn-fardu kifayah epistemological dynamism.